Convertible Securities and Venture Capital Finance - Schmidt, Klaus M. (Journal of Finance, 2003)
AbstractThis paper offers a new explanation for the prevalent use of convertible securities in venture capital finance. Convertible securities can be used to endogenously allocate cash‐flow rights as a function of the state of the world and the entrepreneur's effort. This property can be used to induce the entrepreneur and the venture capitalist to invest efficiently into the project. The result is robust to renegotiation and to changes in the timing of investments and information flows. The model is consistent with the observations that conversion is often automatic and that convertible securities are rarely used by outside investors.